Evaluation of Global South’s efficiency at the Summer Olympics - Julian Alexander Klöcker; Frank Daumann (PLoS ONE, 2025)
States differ significantly in international sports competitions in how they use the resources they have and whether they do so in an efficient manner. In this paper, we investigate the efficiency of the nations from the so-called “Global South”, in total 52 states, during the 2000–2024 Summer Olympics. By doing this, our paper is the first using the Bayesian stochastic frontier analysis for exploring the performance of the states of the Global South. We perform an age decomposition, which shows that the 25–29 and 30–34 age cohorts contribute the most to Olympic performance. Our findings also suggests that transient efficiencies are higher than persistent efficiencies in a majority of the analyzed nations. Our analysis represents an important contribution in analyzing developing states‘ efficiency in elite sports.